2022
DOI: 10.3390/antibiotics11121834
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Virulence Effect of Vismia guianensis against Candida albicans and Candida glabrata

Abstract: In folk medicine, Vismia guianensis is used to treat skin diseases and mycoses in the Amazon region. We evaluated the anti-Candida activity of the hydroalcoholic extract from the leaves of Vismia guianensis (EHVG). HPLC-PDA and FIA-ESI-IT-MSn were used to chemically characterize EHVG. The anti-Candida activity was determined in vitro by the minimum inhibitory concentrations (MIC) against Candida glabrata (ATCC-2001); Candida albicans (ATCC-90028, ATCC-14053, and ATCC-SC5314), and C. albicans clinical isolates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…been used to treat skin diseases, such as herpes, dermatitis, leprosy, syphilis, scabies and eczema, among others [4,[9][10][11][12].…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…been used to treat skin diseases, such as herpes, dermatitis, leprosy, syphilis, scabies and eczema, among others [4,[9][10][11][12].…”
Section: Original Research Articlementioning
confidence: 99%
“…Afrovismia, which includes the African species" [5]. "In Venezuela 17 species of Vismia have been located being Vismia baccifera Triana & Planch and Vismia macrophylla Kunth the most common and well-distributed around the country" [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the study highlights the importance of P. granatum as a source of antimicrobials and the need for further studies with the tannin identified in the study. In another report by Motta et al [ 5 ], C. albicans and C. glabrata were incubated with the hydroalcoholic extract from the leaves of Vismia guianensis , a native Brazilian plant. The extract showed antifungal and fungicidal activities against Candida sp., inhibiting fungi growth and adhesion, as well as disrupting both early and mature biofilms.…”
mentioning
confidence: 99%